Ahmad Moftizadeh and the Idea of the Islamic Government: A Discursive Tradition Analysis in the Field of Political Islam - Abbas Jong; Saman Ebrahimzadeh (Religions, 2024)
This article explores the idea of political Islam as a discursive tradition within the context of Iranian Kurdistan. It challenges the prevailing essentialist and universalist approaches commonly used in the analysis of political Islam, advocating for a more adaptable and comprehensive interpretation. By conceptualizing political Islam as a discursive tradition, this study sheds light on the complex interconnections, configurations, and historical contingencies influencing Islamist discourses and movements. The paper argues that political Islam should be examined in relation to other phenomena and discourses, acknowledging its dynamic nature within specific temporal and spatial contexts. Focusing on an influential yet underexplored Islamist discursive tradition in Iranian Kurdistan during the 1970s and 1980s, the research acknowledges the hybrid nature of Islamist discourses, drawing from diverse traditions to fulfill particular objectives. In particular, it explores the perspectives of Ahmad Moftizadeh, a Sunni Kurdish Islamist and the founder of the Maktab Quran (MQ). This study investigates Moftizadeh’s views on the Islamic government, positioning it within the framework of discursive tradition. It analyzes his core categories and inquiries within Islamist thought, notably emphasizing Moftizadeh’s alignment of the Islamic government with the Islamic tradition of the Shura, highlighting its central role in the Islamist discursive tradition.